The Effects of Financial Development and Institutional Quality on Economic Growth with the Dynamic Panel Data Generalized Moment Method Method: Evidence from the Organization for Economical Cooperation and Development Countries - Ahmadpour Kacho, Ali; Dahmardeh, Nazar (International Journal of Economics and Financial Issues, 2017)
Institutional quality and financial development have been considered as two main key of economic growth in recent literature. Regarding institutional quality, it is an essential and necessary condition to enhance financial development, so in this context suitable policies are demanded. Our main aim is to survey the effects of financial development and institutional quality on economic growth for the case of Economic Development and Cooperation Organization Countries in 2002-2014, using GMM method of Dynamic Panel Data. Here also we have used the mean of opinion and response, political stability and lack of violence, administrative efficiency, quality of provisions and legality and corruption control as six institutional indicators as well as the ratio of available credits for private sector in banks to gross product as financial development indicator. The results show that financial development and institutional quality have a positive and significant effect on economic growth in selected countries. Furthermore, from interactive effect, we found that financial development may cause economic growth in developed countries due to their opportune institutional structure. Keywords: Institutional Quality, Financial Development, Economic Growth JEL Classifications: E44, F4